2008
DOI: 10.1371/journal.pgen.1000228
|View full text |Cite
|
Sign up to set email alerts
|

Condensin II Resolves Chromosomal Associations to Enable Anaphase I Segregation in Drosophila Male Meiosis

Abstract: Several meiotic processes ensure faithful chromosome segregation to create haploid gametes. Errors to any one of these processes can lead to zygotic aneuploidy with the potential for developmental abnormalities. During prophase I of Drosophila male meiosis, each bivalent condenses and becomes sequestered into discrete chromosome territories. Here, we demonstrate that two predicted condensin II subunits, Cap-H2 and Cap-D3, are required to promote territory formation. In mutants of either subunit, territory form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
121
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(135 citation statements)
references
References 53 publications
14
121
0
Order By: Relevance
“…The analysis of GFP-tagged RAE1 distribution in wildtype meiosis I cells indicated co-localization of RAE1 with chromatin starting from late prophase primary spermatocytes until ana/telophase I nuclei, thus suggesting that the role of RAE1 in chromatin condensation may be more direct. In meiosis, bivalents need to reach a correct condensation state during late G2/prophase I to ensure a faithful chromosome partitioning to daughter cells, through the resolution of homologous associations, necessary to prevent chromatin bridges (Hartl et al, 2008). Hence, defective chromosome condensation could explain the lagging chromosomes and anaphase bridges, culminating in an uneven chromosome segregation to the opposite cell poles of the first meiotic division.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of GFP-tagged RAE1 distribution in wildtype meiosis I cells indicated co-localization of RAE1 with chromatin starting from late prophase primary spermatocytes until ana/telophase I nuclei, thus suggesting that the role of RAE1 in chromatin condensation may be more direct. In meiosis, bivalents need to reach a correct condensation state during late G2/prophase I to ensure a faithful chromosome partitioning to daughter cells, through the resolution of homologous associations, necessary to prevent chromatin bridges (Hartl et al, 2008). Hence, defective chromosome condensation could explain the lagging chromosomes and anaphase bridges, culminating in an uneven chromosome segregation to the opposite cell poles of the first meiotic division.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined whether the fivesubunit condensin II complex is present in Drosophila because the gene encoding CAP-G2 has not yet been found in the sequenced region of the Drosophila genome. Currently available evidence suggests that the putative condensin II subunits (CAP-D3 and CAP-H2) may not play a major role in mitotic chromosome organization and segregation (Savvidou et al 2005;Oliveira et al 2007) and that they have meiotic functions instead, making a crucial contribution to anaphase I chromosome segregation (Hartl et al 2008b;see below).…”
Section: Drosophila Melanogastermentioning
confidence: 99%
“…Although mitotic cells express them, it appears that they do not play major functions in mitotic chromosome assembly or segregation (Savvidou et al 2005). Instead, a recent genetic study has shown that both CAP-D3 and CAP-H2 are necessary for male fertility (Hartl et al 2008b). Cap-H2 mutants display defects in chromosome territory formation in prophase I, which in turn result in a failure to resolve heterologous and/or homologous chromosomes in anaphase I.…”
Section: Melanogastermentioning
confidence: 99%
“…Condensin is involved in the expression regulation of the recombinant DNA and transfer RNA genes in budding and fission yeast and in the organization of polytene chromosomes in Drosophila. [22][23][24] Condensin is involved in T-and B-cell development and maintenance of quiescence state by regulating the accessibility of transcription factors to chromatin. 25,26 Many of our knowledge of the roles of condensin in the regulation of interphase chromosome come from studies of the dosage compensation complex (DCC) present in Caenorhabditis elegans.…”
Section: Condensinmentioning
confidence: 99%